Preparation of document tender / Mohd Razif Mustafa - Mustafa, Mohd Razif (Universiti Teknologi MARA, Perak, 2014)
Tender is the process by which bids are invited from interested contractors to carry out specific packages of construction work. It should adopt and observe the key values of fairness, clarity, simplicity and accountability, as well as reinforce the idea that the apportionment of risk to the party best placed to access and manage it is fundamental to the success of a project. The two most commonly used methods of tendering are single stages select selective tendering or two-stage selective tendering. Both involve the invitation of tenders from firm on a pre-approved or ad hoc list, chosen because they meet certain minimum standard in general criteria such as financial standing, experience, capability and competence. The competition element of the tender is provided on the basis of price and quality. The main difference between the two is that in the two-stages process, the contractor becomes involved in the planning of the project at an earlier stages, so they are submitted on the basis of minimal information, and in the second stages the employer's team will develop the precise specification in conjunction with the tenderer. This method is favoured in more complex project, where the contractor may have the significant design input.